Filament Shape Dependent Reset Behavior Governed by the Interplay between the Electric Field and Thermal Effects in the Pt/TiO2/Cu Electrochemical Metallization Device. (11th January 2017) - Kim, Hae Jin; Yoon, Kyung Jean; Park, Tae Hyung; Kim, Han Joon; Kwon, Young Jae; Shao, Xing Long; Kwon, Dae Eun; Kim, Yu Min; Hwang, Cheol Seong
Abstract : The electrochemical metallization (ECM) cell is a feasible contender for high density resistance switching random access memory or neuromorphic devices. This work elucidates the detailed switching model based on the Cu conducting filament (CF) configuration and the interplay between the Joule heating and electric field effects in the Pt/TiO2 /Cu ECM cell, which can explain the switching behaviors both in accordance and discordance with the conventional ECM theory. The Cu CF configuration is varied from the conventional conical one for a small compliance current ( I cc, ≈1 mA) to the hourglass or even cylindrical one by adopting a high I cc value (≈30 mA). The rupture process of the Cu CF can be precisely modeled by considering the mutual constructive interference or the competition between the Joule heating and electric field effects for the rupture and rejuvenation of the Cu CF. These models are supported by an extensive thermal‐field simulation in 2D, and an hourglass‐shaped CF is identified by transmission electron microscopy, which is in accordance with the suggested model with a moderate I cc . The detailed geometry of the formed CF and relative bias polarity during the reset step play a critical role in determining the bipolar or unipolar switching mode. Abstract : The detailed switching model based on the Cu conducting filament (CF) configuration and the interplay between the Joule heating and electric field effects in the Pt/TiO2 /Cu electrochemical metallization cell is illustrated. Detailed geometry of the CF and relative bias polarity during the reset process play a critical role in determining the reset polarity. Simulation results support the model.